2011
DOI: 10.1089/vbz.2010.0072
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence ofStaphylococcus aureusST398

Abstract: The epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) has changed dramatically over the past 15 years. Initially a nosocomial pathogen, newly emergent strains of MRSA have become increasingly common in the community among individuals lacking contact with healthcare. More recently, a third group of MRSA strains have been identified in association with livestock, particularly swine. These strains, termed livestock-associated MRSA, have now been identified in Europe, North America, and Asia in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
161
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(165 citation statements)
references
References 127 publications
3
161
1
Order By: Relevance
“…In an interesting report from the Netherlands, it was shown that farm visitors were positive for CC398 MRSA directly after a farm visit but tested MRSA negative after 24 h [19,41]. These and other studies indicate that CC398 appears to be frequently shared between animals and humans and is capable of causing infections in both species [25,70,164]. Transmission of MRSA between animals and humans is not new, but the MRSA isolates, in most cases, represent an initial human-to-animal transmission [24,49,165,166].…”
Section: Molecular Epidemiology Of S Aureus Cc398mentioning
confidence: 79%
See 3 more Smart Citations
“…In an interesting report from the Netherlands, it was shown that farm visitors were positive for CC398 MRSA directly after a farm visit but tested MRSA negative after 24 h [19,41]. These and other studies indicate that CC398 appears to be frequently shared between animals and humans and is capable of causing infections in both species [25,70,164]. Transmission of MRSA between animals and humans is not new, but the MRSA isolates, in most cases, represent an initial human-to-animal transmission [24,49,165,166].…”
Section: Molecular Epidemiology Of S Aureus Cc398mentioning
confidence: 79%
“…The emergence of LA-MRSA strains in humans [16,17,25,56] and the presence of an identical MRSA CC398 in pigs, farm workers, veterinarians who atended to the same pig farms and their nonexposed family members [47,48] suggests animal-to-human or human-to-animal transmission. In an interesting report from the Netherlands, it was shown that farm visitors were positive for CC398 MRSA directly after a farm visit but tested MRSA negative after 24 h [19,41].…”
Section: Molecular Epidemiology Of S Aureus Cc398mentioning
confidence: 99%
See 2 more Smart Citations
“…6 Over the last few decades, the number and proportion of vancomycin-resistant S. aureus (VRSA) and methicillin-resistant S. aureus (MRSA) infections in different countries has increased. 7,8 Several studies have shown that MRSA strains are highly resistant to antibiotics. [9][10][11] Despite the discovery of new drugs for the treatment of infections caused by VSRA and MRSA, outbreaks of MRSA/VRSA infections often appear in hospitals, clinics, nursing and elderly homes.…”
mentioning
confidence: 99%